2013
DOI: 10.1186/1471-2148-13-70
|View full text |Cite
|
Sign up to set email alerts
|

Diversification of Quiescin sulfhydryl oxidase in a preserved framework for redox relay

Abstract: BackgroundThe enzyme family Quiescin Sulfhydryl Oxidase (QSOX) is defined by the presence of an amino-terminal thioredoxin-fold (Trx) domain and a carboxy-terminal Erv family sulfhydryl oxidase domain. QSOX enzymes, which generate disulfide bonds and transfer them to substrate proteins, are present in a wide variety of eukaryotic species including metazoans and plants, but are absent from fungi. Plant and animal QSOXs differ in their active-site amino acid sequences and content of non-catalytic domains. The qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…It should be noted that there is an additional CXXC motif toward the C terminus of the ERV domain. Although this C V XXC VI motif is conserved in all QSOX sequences examined to date (1,19), single or double mutations at this locus have an insignificant impact on the turnover of protein substrates in vitro using either human QSOX1 or TbQSOX (28,32). Furthermore, the recent crystal structures of open and closed forms of TbQSOX (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that there is an additional CXXC motif toward the C terminus of the ERV domain. Although this C V XXC VI motif is conserved in all QSOX sequences examined to date (1,19), single or double mutations at this locus have an insignificant impact on the turnover of protein substrates in vitro using either human QSOX1 or TbQSOX (28,32). Furthermore, the recent crystal structures of open and closed forms of TbQSOX (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…TbQSOX proves especially tractable to express in Escherichia coli (28), and its three-domain structure represents the minimal architecture for this family of multidomain sulfhydryl oxidases (16,19,28,29). Fig.…”
mentioning
confidence: 99%
“…Analogously, QSOX enzymes have been found in secreted fluids including milk, semen, egg white and blood serum (Hoober et al, 1996 ; Benayoun et al, 2001 ; Zanata et al, 2005 ; Jaje et al, 2007 ). The extracellular QSOXs in different biological systems suggest they may play diverse roles (Limor-Waisberg et al, 2013 ). For instance, it was found that extracellular catalysis of disulfide bond formation by human QSOX1 is needed for laminin incorporation into the extracellular matrix, which is a prerequisite for tumor adhesion and metastasis (Ilani et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Quiescin sulfhydryl oxidase (QSOX) family enzymes, found in eukaryotes except fungi, specifically catalyze the direct and facile introduction of disulfide bonds into unfolded, reduced proteins with the reduction of a molecular oxygen, generating hydrogen peroxide: 2RSH+O 2 → RS-SR+H 2 O 2 (Haque et al, 2012 ; Limor-Waisberg et al, 2013 ). Two moieties of the enzyme carry out the tandem actions of substrate oxidation and electron transfer: thioredoxin-fold (Trx) domain and a sulfhydral oxidase module related to the Erv/ALR enzyme family.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation